Fractional Variational Iteration Method and Adomian’s Decomposition Method: Applications to Fractional Burgers Kuramoto KdV Equation via Hadamard Derivative - Hichem, Djeriba; Kacem, Belghaba (Communications in Mathematics and Applications, 2021)
This paper presents the analytical solutions of the Fractional Burgers Kuramoto KdV equation by the variational iteration method and Adomian’s decomposition method using Hadamard fractional derivative. By using initial conditions, the explicit solutions of the Burgers Kuramoto Kdv equation have been presented. The fractional derivatives are considered according to the Hadamard’s approach. Two examples are given for illustrate to implement variational iteration method and Adomian’s decomposition method for fractional Burgers Kuramoto KdV equation.